Being a sperm donor : masculinity, sexuality, and biosociality in Denmark - Mohr, Sebastian (Fertility, reproduction, and sexuality ;, 2018)
What does it mean to be a man in our biomedical day and age' Through ethnographic explorations of the everyday lives of Danish sperm donors, Being a Sperm Donor explores how masculinity and sexuality are reconfigured in a time in which the norms and logics of (reproductive) biomedicine have become ordinary. It investigates men's moral reasoning regarding donation, their handling of transgressive experiences at the sperm bank, and their negotiations of gender, sexuality, intimacy, and relatedness, showing how the socio-cultural and political dimensions of (reproductive) biomedicine become intertwined with men's intimate sense of self.